2008
DOI: 10.1002/ppul.20853
|View full text |Cite
|
Sign up to set email alerts
|

Effect of secondhand cigarette smoke, RSV bronchiolitis and parental asthma on urinary cysteinyl LTE4

Abstract: Cysteinyl leukotrienes promote airway inflammation, bronchoconstriction and mucus hypersecretion. Cigarette smoking and respiratory syncytial virus (RSV) bronchiolitis are known to increase urinary cysteinyl leukotriene E4 (uLTE4), the end product of the cysteinyl leukotriene biosynthetic pathway. We tested the following hypotheses: (1) Secondhand smoke (SHS) exposure increases uLTE4 in well infants and in those hospitalized for RSV bronchiolitis; (2) Length of hospital stay for those with RSV bronchiolitis co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 32 publications
(34 reference statements)
1
15
0
Order By: Relevance
“…In smokers, uLTE 4 levels correlate with the number of cigarettes smoked [34]. Kott et al [32] found in a significant increase in uLTE 4 excretion in infants with bronchiolitis and ETS exposure. Similar to our results, Rabinovitch et al [35] did not find any differences in uLTE 4 levels between ETS exposed and those who were not, though there were clinical differences, including albuterol usage.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In smokers, uLTE 4 levels correlate with the number of cigarettes smoked [34]. Kott et al [32] found in a significant increase in uLTE 4 excretion in infants with bronchiolitis and ETS exposure. Similar to our results, Rabinovitch et al [35] did not find any differences in uLTE 4 levels between ETS exposed and those who were not, though there were clinical differences, including albuterol usage.…”
Section: Discussionmentioning
confidence: 97%
“…Data quantifying LTE 4 levels in children exposed to ETS is limited [32]. There is some evidence that children with asthma exposed to ETS are more likely to respond to montelukast than ICS, and that montelukast responders tend to have a relatively higher uLTE 4 /FeNO ratio [35,36].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…59,60 These data clearly demonstrate the respiratory risks associated with in utero smoke exposure and reemphasize the priority that should be placed on smoking cessation, especially in pregnant women. 61 Another interesting finding is that almost 40% of the children who required mechanical respiratory support on the day of presentation had difficulty breathing for ,1 day before presentation.…”
Section: Discussionmentioning
confidence: 99%
“…For infants hospitalized with RSV bronchiolitis, Kott et al [133,134] identified several predictors of hospital length of stay: age, urinary cysteinyl leukotriene E4 concentration, and impaired plasma tumor necrosis factor α and interleukin-6 production capacity. For patients hospitalized with bronchiolitis, Hervás et al [58] found virus species (RSV vs. non-RSV) to be a predictor of hospital length of stay.…”
Section: Predicting Hospital Length Of Staymentioning
confidence: 99%